2007
DOI: 10.1111/j.1365-3083.2007.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Long‐term and High‐dose Mould‐exposed Sawmill Workers

Abstract: Exposure to moulds is thought to cause adverse health effects ranging from vague subjective symptoms to allergy and respiratory diseases. Until now, most studies have been emphasizing low levels of exposure. In Norwegian sawmills during the 1980s, extensively high spore counts up to 107 spores/m3 air were reported. By using serum samples obtained from sawmill workers during that period, in addition to control sera, we studied the antibody response of all classes and IgG subclasses to Rhizopus microsporus at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The latter finding is in line with a previous study which showed that mould-exposed sawmill workers with the highest exposure had the lowest levels of sIgE 37. This finding may probably be explained by the healthy worker effect.…”
Section: Discussionsupporting
confidence: 92%
“…The latter finding is in line with a previous study which showed that mould-exposed sawmill workers with the highest exposure had the lowest levels of sIgE 37. This finding may probably be explained by the healthy worker effect.…”
Section: Discussionsupporting
confidence: 92%
“…However, reports on R. microsporus-related infections are relatively uncommon compared with reports on infections related to other Rhizopus species. It has been associated with moldy lumber, as evidenced by the presence of serological responses to Rhizopus species among sawmill workers (37,38). It has also been found in the wooden material used for patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal administration of the drug betamethasone was associated with an increase in UCB of retinol-binding protein, transthyretin, and transferrin (Georgieff et al 1988). Increased levels of IgG were found to be associated with a range of environmental exposures—for example, to mold (Rydjord et al 2007), organochlorines (Karmaus et al 2005), tobacco-smoke products (Colquhoun et al 2009), and methylmercury (Nyland et al 2011). …”
Section: Discussionmentioning
confidence: 99%